A Statistical analysis study on Coca-Cola Bottlers Philippines, Inc. Santa Rosa Plant II - Abella, Scott Alexander P.; Castro, Karlo Eugene Josef M.; Magsuci, Kristoffer Immanuel B. (Diliman, Quezon City College of Engineering, 2002)
Coca Cola Bottlers Philippines Inc. is the country's leading soft drink manufacturer. Santa Rosa Plant II is the country's sole manufacturer of canned Coca Cola products. In order to maintain the high level of quality in its products, different factors are addressed by the plant. One of these is the level of gas volume present in beverages. Gas volume determines the amount of fizz of which the soft drink is known for. Gas volume can be further studied into two important factors : dissolved oxygen level, expressed in parts per million (ppm) and beverage temperature level, expressed in degree celcius. Problem identification and Statistical tools such as Ishikawa diagram, Pie charts, Goodness of Fit test, ANOVA table, Runs Test of randomness, Duncan's Multiple Range test, Two-sample Sign Tests, Effects Analysis and Regression modeling were utilized to arrive at a specific solution.A Two-Factor Factorial Design determined which factors really affect the gas volume and whether the interaction of two factors produces a significant effect. ANOVA showed that the level of dissolved oxygen and the solution temperature both have significant effects on the beverage gas volume. Duncan's Multiple Range Test and the Two-sample Sign Tests indicated that there is a significant difference in the gas volume means selected temperatures. Regression modeling enabled the project proponents to construct a model for the gas volume of the beverage against the solution temperature. Through the statistical analysis performed, it was found that the level of gas volume positively reacts to the beverage temperature, and negatively reacts on the amount of dissolved oxygen on the beverage. The project proponents therefore recommended that the company regularly monitor the temperature of the solution since there is a dependence of gas volume to solution temperature. It was also recommended the better control and monitoring should occur in dissolved oxygen level analysis. The company should monitor and identify the allowable range of dissolved oxygen, which significantly affects gas volume in product A.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics